2015
DOI: 10.1037/pas0000111
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the heterogeneity of impulsivity: A meta-analytic review of the behavioral implications of the UPPS for psychopathology.

Abstract: The construct of impulsivity is implicated in a wide variety of psychopathology. However, the heterogeneous factors or subcomponents that differentially predict outcomes are still in the process of being parsed. The present review and meta-analysis focuses on the psychopathological correlates of the Negative Urgency, (lack of) Premeditation, (lack of) perseverance, Sensation Seeking, and Positive Urgency (UPPS/UPPS-P; Whiteside & Lynam, 2001). which provides a relatively new model of impulsivity that posits 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

34
458
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 488 publications
(505 citation statements)
references
References 196 publications
(184 reference statements)
34
458
2
11
Order By: Relevance
“…It was due to multicollinearity that Blain et al needed to separate negative and positive urgency and analyse two regression models. Other studies [24,27,28] have also found correlations consistently appearing above r=0.60 between positive and negative urgency which supports Berg et al [2] questioning the distinctiveness of these two impulsivity facets.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…It was due to multicollinearity that Blain et al needed to separate negative and positive urgency and analyse two regression models. Other studies [24,27,28] have also found correlations consistently appearing above r=0.60 between positive and negative urgency which supports Berg et al [2] questioning the distinctiveness of these two impulsivity facets.…”
mentioning
confidence: 53%
“…Of particular interest to the current study was the positive urgency facet and claims that it may not be orthogonal to negative urgency [2]. In the current study, both negative and positive urgency were strongly correlated with both the PGSI and impaired control.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations